PERANAN KEGIATAN PEMANENAN KAYU DALAM MENINGKATKAN PENDAPATAN MASYARAKAT SEKITAR HUTAN: KASUS DI KPH SUKABUMI DAN KPH CIANJUR - Ishak Sumantri; Sukadaryati Sukadaryati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Timber harvesting activities in Perhutani areas are conducted with the involvement of people living around the forest. An investigation was conducted to find out the role of timber harvesting activities in increasing the income of people involved. The results showed that 1) People living around the forest were involved in felling, skidding, and collecting log in temporary logyard; 2) Workers involvement were temporary and their wage system were differed from location to location. In Sukabumi, the whole work contract system was applied with the income ranging from Rp 109.800 to 187.417/person/compartment or Rp 13.725 to Rp 23.500/person/day. In Cianjur, the piece work system was applied with income ranging from Rp 97.788 to 179.166/person/compartment or Rp 5.750 to Rp 10.500/person/day; and 3) The income obtained from timber harvesting activities still can not significantly increase worker's income and, therefore, it is necessary to furthur seek a proper model suitable for the need of temporary and low income workers to participate in managing forest in Perhutani areas.